Sigtuna Think Piece 2: Climate Capabilities and Climate Change Education Research - David O. Kronlid (Environmental Association of Southern Africa, 2009)
This think piece introduces the views of Amartya Sen, Martha Nussbaum and others on the capabilities approach to climate change ethics research. Furthermore, it suggests that the capabilities approach can help climate change research in identifying if, and if so which, intrinsic values of people's wellbeing are vulnerable to climate change. The think piece introduces a climate-capabilities reading of documents associated with the IPCC Fourth Assessment Report (IPCC, 2007). Furthermore, it suggests that climate change education research may include descriptive and comparative, normative, critical and meta forms of research to investigate the various meanings of climate change wellbeing in spaces of capabilities. Furthermore, climate change education research may contribute to climate change research in identifying how education may help students identify individual, social and environmental conversion factors. That is, factors needed to convert, for example, adaptation resources into actual beings and doings - into climate capabilities.